#TEMANLEBIHBAIK : KAMPANYE DIGITAL KALLA GROUP DI INSTAGRAM - Yanti, Trisna; Uliviana Restu Handaningtias (Jurnal Netnografi Komunikasi, 2024)
The current environmental problems require increased awareness from all parties, including the people of Sulawesi. Awareness of the environment, especially the reduction of plastic use, can be achieved by using digital campaigns as Kalla Group has done through the #TemanLebihBaik campaign on Instagram. This research seeks to see how Kalla Group's Instagram attracts public interest in the campaign to raise awareness of environmental awareness and reduce the use of plastic by using Chris Heuer's 4C theory. The method used is netnography with a qualitative approach. The results of this study show that the #TemanLebihBaik campaign content has implemented Chris Heuer's 4C theory, namely context, communication, collaboration, and connection. And the conclusion is that Kalla Group can increase awareness of environmental care and reduce the use of plastic, but if seen from the number of participants who are not proportional to the number of likes of the highest content. So Kalla Group has not been maximized in attracting public interest in participating in the #TemanLebihBaik campaign.